A Study of Women's Opinions after Relocation: Women from Kalijodo at Pulogebang Flats (Oratio Directa, 2018)
This study examines the opinions of women affected by the relocation of Kalijodo residents to Pulogebang Flats. Public opinion is treated as a central concept in political communication, while the analysis is limited to women’s experiences as a socially marginalized group. Using a qualitative case-study approach and Muted Group Theory, data were collected through participant observation and in-depth interviews with five women who had lived in Kalijodo. The findings show that economic opportunities, residential facilities, and relations with flat management constrained the women’s ability to express their aspirations.
Keywords: Women’s Opinion; Relocation; Kalijodo; Muted Group Theory; Political Communication